Environmental Performance and Firm Size: Profitability as a Moderator Variable - Siregar, Fachrul A; Taufiqurrahman (Universitas Bhayangkara Surabaya, 2025)
This research analyze the effect of Environmental Performance on Firm Size with Profitability as a moderating variable in energy and mining subsector companies listed on the Indonesia Stock Exchange for the 2021–2024 period. A quantitative approach was applied using purposive sampling on 10 emiten that consistently publish sustainability reports, resulting in 40 observations. Data were analyzed using classical assumption tests, multiple linear regression, t-tests, F-tests, and Moderated Regression Analysis (MRA). The results show that Environmental Performance has a positive and significant effect on Firm Size. Furthermore, Profitability strengthens this relationship, as indicated by the increase in the coefficient of determination after the interaction variable is included. These findings support legitimacy theory and indicate that companies with strong environmental performance and high profitability are more likely to grow and expand their operational scale. These results are important as strategic input for companies in designing sustainability policies that support long-term growth.